Iron cobalt selenide counter electrode for application in dye‑sensitized solar cell: synthesis parameter, structural, electrochemical, and efficiency studies - Mohd Noor, Ikhwan Syafiq; Tan, Winie; Najihah, M. Z.; Saaid, Farish Irfal; H. J., Woo (Springer Nature, 2024)
This work reports on the synthesis of FeCo2Se4 from FeCo2O4 by varying the duration of the selenization process. The structure and crystallinity of the products were characterized using X-ray difraction (XRD). Energy dispersive X-ray spectroscopy (EDX) analyzed the compositions of the products. The FeCo2O4 presents a thinner and smoother nanosheets structure whereas the FeCo2Se4 forms a thicker and rougher nanosheets structure. The electrocatalytic efects of FeCo2Se4 and FeCo2O4 in comparison to Pt were examined by cyclic voltammetry (CV) and further supported by Tafel polarization. Electrochemical impedance spectroscopy (EIS) was employed to study the internal resistance and charge transfer kinetics. The FeCo2Se4 obtained after 12 h selenization treatment (FeCo2Se4) exhibits the highest electrocatalytic activity and the lowest charge transfer resistance, followed by Pt and FeCo2O4. The poly(vinylidene fuoride-co-hexafuoropropylene) (PVdFHFP)/ propylene carbonate (PC)/ 1,2-dimethoxyethane (DME)/ 1-methyl-3-propyl imidazolium iodide (MPII)/ sodium iodide (NaI)/ iodine (I2) gel polymer electrolytes were assembled into dye-sensitized solar cells (DSSCs) with titanium oxide (TiO2) photoanode and the respective counter electrode. The respective counter electrode was FeCo2Se4, FeCo2O4, or platinum (Pt). The efciencies attained for FeCo2Se4, FeCo2O4, and Pt counter electrodes are 8.71, 6.04, and 6.11%, respectively. Superior cell efciency with FeCo2Se4 counter electrode can be attributed to the higher porosity, larger specifc surface area, lower electron transfer resistance, and higher I3 − reduction rate of FeCo2Se4.